БЎЛАЖАК ФИЗИКА ЎҚИТУВЧИСИНИНГ МЕТОДИК ТАЙЁРГАРЛИГИНИ КОМПЕТЕНЦИЯВИЙ ЁНДАШУВ АСОСИДА РИВОЖЛАНТИРИШ - Карлыбаева, Г.Е. (SCIENCE and SOCIETY, 2020)
The article provides information on the development of methodological training of future teachers in physics through the use of a competency-based approach (communicative, informational, socially active citizenship, general cultural and mathematical literacy, awareness and use of scientific and technical news).
Keywords: future teachers of physics; methodological training; competency-based approach; competence